Language, power, and democracy in presidential discourse: a critical discourse analysis - Amon Bernabas Tenis; Metria Dicky Putra; Iskandar Iskandar (Indonesian Reseacher for Language Learning and Teaching, 2026)
This research presents the analysis of the statement made by the President of Indonesia on August 31, 2025, amid political protests and social turmoil. It seeks to investigate how the discourse reflects democracy using Norman Fairclough’s Critical Discourse Analysis (CDA) framework. The study employs a descriptive qualitative methodology and examines speech across three aspects: text, discourse practice, and socio-cultural practice. At the textual level, the president employs imperative forms, modal verbs, and interfaith salutations to establish authority while conveying a sense of inclusiveness. Within the realm of discourse practice, the assertion serves as a compelling tool that presents elite agreement as being attentive to the desires of citizens, disseminated widely through media to shape public opinion. At the socio-cultural level, it illustrates Indonesia’s democratic contradiction, acknowledging freedom of speech while strengthening governmental authority. The analysis shows that the speech depicts democracy as a combination of freedom and discipline, along with solidarity and order. The research finds that political discourse transmits governmental stances while also maintaining hegemonic legitimacy. It additionally recommends that upcoming studies examine how media framing enhances or challenges presidential communication and analyze comparable addresses across crises to deepen insights into language, authority, and democracy in Indonesia